Co-activation alters the linear versus non-linear impression of the EMG-torque relationship of trunk muscles - Brown, S. H. M.; McGill, S. M. (Journal of Biomechanics, 2008)
The use of electromyographic signals in the modeling of muscle forces and joint loads requires an assumption of the relationship between EMG and muscle force. This relationship has been studied for the trunk musculature and been shown to be predominantly non-linear, with more EMG producing less torque output at higher levels of activation. However, agonist-antagonist muscle co-activation is often substantial during trunk exertions, yet has not been adequately accounted for in determining such relationships. The purpose of this study was to revisit the EMG-moment relationship of the trunk recognizing the additional moment requirements necessitated due to antagonist muscle activity. Eight participants generated a series of isometric ramped trunk flexor and extensor moment contractions. EMG was recorded from 14 torso muscles, and the externally resisted moment was calculated. Agonist muscle moments (either flexor or extensor) were estimated from an anatomically detailed biomechanical model of the spine and fit to: the externally calculated moment alone; the externally calculated moment combined with the antagonist muscle moment. When antagonist activity was ignored, the EMG-moment relationship was found to be non-linear, similar to previous work. However, when accounting for the additional muscle torque generated by the antagonist muscle groups, the relationships became, in three of the four conditions, more linear. Therefore, it was concluded that antagonist muscle co-activation must be included when determining the EMG-moment relationship of trunk muscles and that previous impressions of non-linear EMG-force relationships should be revisited.